Kemampuan Literasi Numerasi Siswa SMA Kelas XII IPS - 6 dalam Mata Pelajaran Matematika - Muhammad Lorna Maulia; Fatimatus Zahro; Redita Putri Ermawan; Ulil Nurul Imanah; Reny Widyastutik (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study uses a descriptive method with a quantitative approach to analyze the numeracy literacy ability of grade XII IPS-6 students at SMAN 1 Mojosari. The sample consisted of 34 students who were selected using the purposive sampling technique. This research began with the identification of the problem of low numeracy literacy in mathematics. A numeracy test in the form of 8 story questions related to statistics is given as a pretest to measure students' abilities. The data was analyzed using statistical tests with the help of SPSS to test the validity, reliability, and results of the pretest. The results showed that 73.53% of students were in the advanced category, and 26.47% of students were in the capable category. Students are able to do histogram-shaped problems well, but have difficulty in presenting data in polygon form. These findings support previous research that states that students often have difficulty processing information from graphs and tables. Other factors that affect students' ability to flip